2014
DOI: 10.1007/s10758-014-9241-5
|View full text |Cite
|
Sign up to set email alerts
|

Turning Transfer Inside Out: The Affordances of Virtual Worlds and Mobile Devices in Real World Contexts for Teaching About Causality Across Time and Distance in Ecosystems

Abstract: Reasoning about ecosystems includes consideration of causality over temporal and spatial distances; yet learners typically focus on immediate time frames and local contexts. Teaching students to reason beyond these boundaries has met with some success based upon tests that cue students to the types of reasoning required. Virtual worlds offer an opportunity to assess what students actually do in a simulated context. Beyond this, mobile devices make it possible to scaffold and assess learning in the real world. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In related work, we also tested the idea of offering students “Virtual Binoculars” on a mobile device as part of an ecosystems curriculum intervention so that students could view the upper watershed approximately 20 miles away when they stood at a local reservoir. It made a significant difference in the kinds of questions that students asked about impacts on the reservoir with greater attention to the possibility of distal impacts (Grotzer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In related work, we also tested the idea of offering students “Virtual Binoculars” on a mobile device as part of an ecosystems curriculum intervention so that students could view the upper watershed approximately 20 miles away when they stood at a local reservoir. It made a significant difference in the kinds of questions that students asked about impacts on the reservoir with greater attention to the possibility of distal impacts (Grotzer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Grotzer and colleagues also found that students often reason about immediate effects rather than cascading or indirect effects. They fail to realize that a change in one population can have impacts on populations that are not directly linked through domino-like or cyclic complex causal relationships (Grotzer & Basca, 2003;Grotzer et al, 2015). Grotzer and Tutwiler (2014) outlined a number of characteristics of complex systems that may contribute to these learning challenges.…”
Section: Understanding Complex Systemsmentioning
confidence: 99%
“…However, we argue that content within a crosscutting concept can also be ordered in a learning progression to facilitate learning. Within the science education literature, learning about systems phenomena has most notably been anchored in the study of complex systems (Grotzer et al, 2015;Wilensky & Rand, 2015;Yoon, 2011;Yoon, Goh, & Park, 2018), which investigates how interactions between system components at lower scales give rise to higher scale processes and structures (Sweeney & Sterman, 2007;Wilensky & Reisman, 2006;Yoon, 2008). The way that schools of fish move through the water and herds of ungulates roam the savannah provide vivid examples of how individual actions and interactions lead to large-scale patterns.…”
mentioning
confidence: 99%
“…Augmented reality can be used to alert students to an opportunity to observe something meaningful that connects with ideas they have been learning; and tips, reminders, and reflective prompts embedded in the experience can encourage students to adopt practices of observation that mirror those used by experts (Klopfer and Squire , Dunleavy and Dede , Grotzer et al. ).…”
Section: Why Use Augmented Reality To Support Outdoor Learning About mentioning
confidence: 99%
“…Augmented reality visualizations can be used to communicate changes over time by embedding views or narratives that describe the history of a place (Zimmerman and Land , Grotzer ), or by pointing to evidence of change over time that may be present within the landscape. Ecosystems can have long “memories”—the abiotic conditions, species composition, and relationships present may depend on what happened at the site last season or long ago.…”
Section: Why Use Augmented Reality To Support Outdoor Learning About mentioning
confidence: 99%